INVESTIGATING EFL STUDENTS’ PERCEPTIONS OF THE USEFULNESS OF CANVAS LMS: A CASE STUDY - Mira Nurmala Sari; Asri Siti Fatimah; Melisa Sri (Universitas Perjuangan Tasikmalaya, 2020)
This study aims to investigate students' perceptions of the usefulness of Canvas LMS in Sociolinguistic courses. This study involved three students of English Education at a university in West Java, Indonesia. The data collection method used was the semi-structured interview. Data were analysed using Thematic Analysis with the Braun and Clarke analysis framework. The research results are divided into three aspects, namely the ease and beneficial features for learning, interesting ways to access course material and independent learning skill development. The finding discusses the usefulness of Canvas LMS as a learning medium in Sociolinguistic courses. Therefore, the results of this study provide empirical insight for other students about the benefits of using Canvas LMS in learning that will help them use technology that can support their learning. Keywords: Student Perception, Usefulness, Canvas LMS